2021
DOI: 10.2188/jea.je20190338
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of Gestational Diabetes Mellitus Screening: A Systematic Review

Abstract: Background This study aims to find evidence of the cost-effectiveness of gestational diabetes mellitus (GDM) screening and assess the quality of current economic evaluations, which have shown different conclusions with a variation in screening methods, data sources, outcome indicators, and implementation in diverse organizational contexts. Methods Embase, Medline, Web of Science, Health Technology Assessment, database, and National Health Service Economic Evaluation Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The conflicting recommendations from expert groups underscore the fact that there are data to support each strategy. A systematic review of economic evaluations of GDM screening found that the one-step method identified more cases of GDM and was more likely to be costeffective than the two-step method (254). The decision of which strategy to implement must therefore be made based on the relative values placed on factors that have yet to be measured (e.g., willingness to change practice based on correlation studies rather than intervention trial results, available infrastructure, and importance of cost considerations).…”
Section: Future Considerationsmentioning
confidence: 99%
“…The conflicting recommendations from expert groups underscore the fact that there are data to support each strategy. A systematic review of economic evaluations of GDM screening found that the one-step method identified more cases of GDM and was more likely to be costeffective than the two-step method (254). The decision of which strategy to implement must therefore be made based on the relative values placed on factors that have yet to be measured (e.g., willingness to change practice based on correlation studies rather than intervention trial results, available infrastructure, and importance of cost considerations).…”
Section: Future Considerationsmentioning
confidence: 99%
“…Nonetheless, some authorities, notably the National Institute for Clinical Excellence (NICE) in the UK, still promote risk factor based screening ( 29 ). The most recent Cochrane review ( 30 ) is inconclusive, but a recent systematic review of economic evaluations of GDM screening again concluded that universal screening was the most effective approach ( 31 ). Compliance with officially endorsed risk factor based screening protocols appears to be poor in countries as diverse as Sweden ( 32 ), where only 31% of women received the screening test deemed appropriate for their documented risk factor profile, the UK (61% appropriate screening according to risk factors) ( 33 ) and South Africa ( 34 ), where Adam et al reported that, although use of risk factors would reduce OGTTs by 46%, this protocol would miss 41% of GDM diagnoses ( 34 ).…”
Section: Diagnosis Of Gdmmentioning
confidence: 99%
“…Another option to improve GDM diagnostics would be universal screening, ensuring that every woman is at least offered testing. Universal testing would result in the maximum number of GDM cases at the expense of increased healthcare costs and the workload of clinical personnel; however, overall, this tends to be cost-effective [ 26 ]. As GDM also bears responsibility for long-term complications, mothers and offspring would benefit from universal screening and lifestyle interventions when considering their health risks in later life.…”
Section: Discussionmentioning
confidence: 99%